Pelatihan Pembuatan Sabun Ramah Lingkungan dari Kulit Rambutan Sebagai Agen Kewirausahaan bagi SMAN 2 Pasuruan - Wijaya, Dika Putra; Zakia, Neena; Danar, Danar; Maghfiroh, Ainun; Putri, Ghaitsa Zahira Shofa Pradana; Mahgfiro, Intan Dini; Hasan, Muhammad Ainur; Rahmawati, Ulfa (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
One of the important competencies to be mastered by students in the 21st century is entrepreneurial competency. The development of entrepreneurship for students is related to the natural potential in Pasuruan City, namely rambutan skin in training and mentoring. With this training activity, students of SMA Negeri 2 Pasuruan learn about the role of the creative economy industry or entrepreneurship according to potential trends in business development. The implementation method is through socialization and training in making environmentally friendly liquid soap and providing some materials on solutions regarding the use of liquid soap, especially at SMAN 2 Pasuruan to be trained in making liquid soap at SMAN 2 Pasuruan. The delivery of general description material about soap, things to consider in the content of soap ingredients, soap making training, to mentoring and discussions between students and Lecturers/Students. Based on the implementation of community service activities that have been carried out, namely increasing the understanding of students and teachers of SMAN 2 Pasuruan in producing soap that has the potential to help product development ideas and improve the quality of products from rambutan skin by encouraging soap making.